Music Intervention in Pain Relief of Cardiovascular Patients in Cardiac Procedures: A Systematic Review and Meta-analysis. Issue 11 (29th May 2020) - Wang, Yiru; Wei, Jing; Guan, Xinzhu; Zhang, Yifan; Zhang, Yiyi; Zhang, Na; Mao, Meijiao; Du, Wenting; Ren, Yajuan; Shen, Hong; Liu, Ping
Abstract: Background: Numerous meta-analyses have been conducted on music and pain, but no studies have investigated music and cardiac procedural pain. Objective: To assess the effects of music intervention on pain in cardiac procedures in the published randomized controlled trials. Methods: This study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. All the included randomized controlled studies were published between 1999 and 2016. Studies were obtained from electronic databases or by hand-searching of related journals and reference lists. The main outcome was pain intensity, and the secondary outcomes were vital signs such as heart rate, respiration rate, systolic blood pressure, and diastolic blood pressure. Risk of bias of the included studies was evaluated according to the Cochrane Collaboration guidelines. Results: Analysis of 14 studies indicated that music interventions had statistically significant effects on decreasing pain scales (mean deviation [MD] = –1.84), heart rate (MD = –2.62), respiration rate (MD = –2.57), systolic blood pressure (MD = –5.11), and diastolic blood pressure (MD = 0.44). The subgroup analysis method was used in all five outcomes. Conclusions: Considering all the possible benefits, music intervention may provide an effective complement for the relief of cardiac procedural pain.